Labeling dan Packaging Camilan PAY Mart untuk Kemandirian Ekonomi PAY Putri Aisyiyah Yogyakarta: PAY Mart Snack Labeling and Packaging for PAY Putri Aisyiyah Yogyakarta's Economic Independence - Lestari Rahayu; Nur Rahmawati; Diah Rina Kamardiani (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2022)
Packaging and labeling are important points in selling an item. Initially, the packaging functioned as a place to make it easier to carry a product. However, the packaging is needed over time to encourage buyers' buying interest. In planning the packaging, it is not only an initial plan but also an idea that can show the advantages of a product so that it shows a design that can "sell." The appearance of the packaging must attract consumer interest. So far, the quality of snack product packaging at PAY Mart is still standard and unattractive. Business actors still lack knowledge about good and safe packaging, what information should be on a package, and attractive packaging and packaging forms. This service aims to provide knowledge and skills in making product packaging, from designing designs and making patterns to how to package the musrifah at the Putri Aisyiyah Orphanage and providing training on making halal and tayibah snacks. The method used is counseling and training in making packaging and snack designs. The results of understanding about packaging and labeling, namely 90% of musrifahs understand and 55% of snacks at PAY Mart are packaged by PAY musrifah Aisyiyah Putri Yogyakarta.